ANALISIS KINERJA BANK UMUM SYARIAH DENGAN MENGGUNAKAN PENDEKATAN CAMEL DAN PENDEKATAN ISLAMICITY PERFORMANCE INDEX TAHUN 2013-2018 - Yolanda, Rista; Verdiyanti, Verdiyanti; Andjioe, Oscar Ryanandi (Jurnal Keuangan dan Perbankan Syariah, 2020)
The method used in this research is descriptive method using quantitative. The data source used is secondary data. Results: the performance of Islamic banks with the standard approach of financial ratios 2013-2018 showed"Very Healthy" with an average of 18%. Then when viewed from the NPF showed the predicate "Healthy" with an average of 3.5%. The REO which shows the predicate that is "Very Healthy" with an average of 72%. The ROA shows the predicate that is "Fairly Healthy" with an average of 0.5% and the last from STM which shows the predicate "Healthy" with an average of 24%. The performance of Islamic Commercial Banks shows "Good" from the PSR with an average of 46 %. then if seen from the ZPR value shows the predicate "Not Good" with an average of 0.02% and then seen again from the value of the EDR y which shows a predicate that is "Very Good" with an average of 130% whereas when viewed from the DEWR value indicates a predicate that is "Not Good" with an average of 5% and lastly seen from the value of the IIC it shows an "Very Good" with an average of average of 100%. Conclusion: The concept of Baitul Mal Village itself has characteristics similar to BMT (Baitul Mal Wat Tamlik), the difference in the source of funds derived from the government and the object of the user funds specifically aimed at the local village community